Implementing Project-Based Learning to the Students’ Learning Outcomes - Mantra, Ida Bagus Nyoman; Eno, Celfiani (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
The selection of appropriate and ideal learning models by teaching staff or teachers so that they can be applied in the teaching and learning process is a fundamental factor that significantly influences student interest and achievement of learning outcomes. Several learning models can be applied in schools' teaching and learning process, one of which is the learning model Project Based Learning (PjBL). This research was conducted due to the student's lack of interest and learning outcomes caused by conventional learning methods, which seemed less effective and monotonous, so students did not play an active role in learning. This can be seen from the average student learning outcomes in learning about introducing myself who have not reached the minimum learning criterion so that the learning model is applied Project Based Learning (PjBL) is expected to be a solution-appropriate, effective, and efficient way to increase student interest and learning outcomes in English subjects, especially material Introducing Myself in the classroom. The research method used in classroom action research is the learning model PBjL. This is qualitative research. Based on the results of data analysis in the field, it was found that the use of learning models PBjL can increase the interest and learning outcomes of the students about introducing myself until the learning model PBjL teachers can apply it in learning activities in the classroom because it can increase student interest and learning outcomes.